Microbial biotechnology - Glazer, Alexander N (Cambridge University Press, 2007)
Microbial diversity -- Microbial biotechnology: scope, techniques, examples -- Production of proteins in bacteria and yeast -- The world of "omics" : genomics, transcriptomics, proteomics, and metabolomics -- Recombinant and synthetic vaccines -- Plant-microbe interactions -- Bacillus thuringiensis (Bt) toxins: microbial insecticides -- Microbial polysaccharides and polyesters -- Primary metaboloites: antibiotics and more -- Biocatalysis in organic chemistry -- Biomass -- Ethanol -- Environmental applications.; Includes bibliographical references and index